Learning Analysis of the Long Jump Material Using the Playing Method for Junior High School Students - Rubi Yatno; Rahmat Putra Perdana; Edi Purnomo; Eka Supriatna; Putra Sastaman (JURNAL SERAMBI ILMU, 2022)
This study aims to determine how the learning outcomes of the squat style long jump using the play method in class VIII students of State Junior High School 1 Kuburaya. The form of research used in this research is experimental research with two stages consisting of planning, implementation, observation, reflection, and conclusion. The subjects in this study were Class VIII students, totaling 35 students. The results of improving soccer passing learning using the inside of the foot are obtained by comparing the observation value with the initial test before the action known as "pre-stage" and the score at stage 1 then stage 2. Based on the results of observations that have been carried out, there is an increase in student scores, namely in the pre-stage completeness of students only reached 28% then at stage 1 the completeness increased to 50% and at stage 2 there was an increase in completeness to 84% it can be concluded that the playing method applied was successful in improving students' long jump learning outcomes. Playing has been proven to improve learning the squat style long jump. This is evidenced by the increase in the squatting style long jump learning which is quite good, which is an increase in student scores at each stage.